Prevalence, locations and predictors of attitudes accepting both intimate partner violence and additional forms of violence against women and girls in South Sudan: a geospatial analysis. - Angelo Lamadrid; Ignacio Leiva-Escobar; Caroline Jeffery; Robert J Anguyo; Richard Lako; Joseph J Valadez (PLOS Global Public Health)
Most research on violence against women and girls (VAWG) in South Sudan has focused on intimate partner violence (IPV) neglecting other forms of VAWG. This research aims to determine the prevalence of attitudes accepting IPV and whether it overlaps with attitudes accepting additional forms of VAWG (child marriage, raiding villages for women during cattle rustling or other raids or female genital mutilation) in South Sudanese men and women, or are different attitudinal phenomena. We used data from the National Household Survey South Sudan 2020 (n = 1,732 women, n = 1,730 men aged 15-49 years). We estimated attitudinal prevalences and applied spatial analysis (Global Moran's I, Getis and Ord's local Gi*, and Kuldorff's SatScan) and multilevel regression to assess overlapping attitudes accepting IPV and at least one other form of VAWG studied in the 10 states and three administrative areas comprising the country. The prevalence of attitudes accepting IPV overlapping with the prevalence of attitudes accepting at least one other form of VAWG was 34.72% (95% CI = 33.14%-36.34%). Sub-national results were non-randomly correlated (Global Moran's I= 0.23). Higher clusters displaying overlaps were located in the counties Kapoeta East, Kapoeta South, Kapoeta North, Budi, Pibor, and Ikotos. People married, cohabiting or living together (aOR = 1.40, 95% CI = 1.04-1.90) as well as people widowed, divorced or separated (aOR = 1.75, 95% CI = 1.05-2.93) were associated with attitudinal overlaps. Conversely, communities with any formal education were associated with a lower odds of overlapping (aOR = 0.26. 95% CI = 0.09-0.70). In South Sudan overlapping acceptance of IPV and at least one other form of VAWG are spatially clustered. Therefore, strategies to understand and tackle them should be strengthened especially in those locations. Essential elements include increasing schooling for children and promoting women's empowerment, especially among male-female partnerships. These conclusions have national and international policy implications.